2019
DOI: 10.1002/slct.201803829
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Cr3+ on Layered Double Hydroxide Supported Cu0 Nanoparticles for the Oxidation of Alcohols and Hydrocarbons

Abstract: Chromium(III)‐doped layered double hydroxide supported copper nanoparticles (Cr3+‐Cu0/LDH) has been prepared as an efficient and reusable catalyst using simple and versatile synthetic method. Effect of doping of Cr3+ to the layered double hydroxide supported Cu0 nanoparticles was evaluated for the oxidation of alcohols and hydrocarbons by varying the amount of Cr3+ loading in the catalyst. The catalyst with Cu:Cr ratio= 1:1 afforded highest catalytic activity among the synthesized catalysts towards the oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…The surface also had some imperfections, indicating that it had a high adsorption capacity. The SEM images also showed that the crystallinity of the nanocatalyst corresponded to the XRD pattern’s characteristic reflections Figure e,f shows the chemical composition of the nanocatalyst as determined by EDX analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The surface also had some imperfections, indicating that it had a high adsorption capacity. The SEM images also showed that the crystallinity of the nanocatalyst corresponded to the XRD pattern’s characteristic reflections Figure e,f shows the chemical composition of the nanocatalyst as determined by EDX analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM images also showed that the crystallinity of the nanocatalyst corresponded to the XRD pattern’s characteristic reflections. 24 Figure 2 e,f shows the chemical composition of the nanocatalyst as determined by EDX analysis. The nanocatalyst, CuNPs@LDH, contains carbon, oxygen, zinc, aluminum, and copper metals, indicating that a heterogeneous nanocatalyst has successfully synthesized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten years ago, ruthenium hydroxide supported on silica was used as an efficient catalyst for the aerobic oxidation of monoterpene alcohols ( Costa et al, 2011 ). Recently, layered double hydroxide-supported Cu 0 nanoparticles ( Choudhary et al, 2019 ), Au nanoparticles ( Karimi et al, 2020 ), and polymeric ionic liquid microspheres/Pd nanoparticles ( Wu et al, 2020 ) have been designed for the oxidation of alcohols. It was presented that primary and secondary alcohols can be efficiently oxidized using CoFe 2 O 4 @HT@Imine-Cu II and TEMPO in the air atmosphere ( Salimi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%